Attachment Styles Among Young Adults: Does Childhood Trauma And Social Support Counts? - Enyelunekpo R. Roberts; Oluwunmi A. Obisesan; Comfort S. Atota; Emmanuel E. Uye (International journal of technology and education research, 2026)
Attachment styles are the foundation on which adult emotional health and interpersonal relationships are built. Studies linking childhood trauma and social support on attachment styles among young adults in Nigeria are lacking. Therefore, this study examines the predictive roles of childhood trauma and social support on attachment styles among young adults in Port Harcourt metropolis. Cross-sectional survey design was utilized while simple random sampling technique was used to select five communities in Port Harcourt metropolis. Data were collected from 278 participants using validated questionnaires and analyzed with multiple regression analysis to test one hypothesis accepted at p =.001 level of significance. The result indicates that childhood trauma and social support jointly predicted attachment styles among study participants, R2 = .274, F(2,275) = 27.50, p = 001. Furthermore, the results reveal that childhood trauma (β = .312, t = 3.59, p =.001) and social support (β = .281, t = 3.30, p =.001) independently predicted attachment styles among study participants. The study concludes that childhood trauma and social support are strong predictors of attachment styles among young adults in Port Harcourt metropolis. The study recommends that primary caregivers should provide a conducive social support system for young adults who have been traumatized to improve their adult relationship.